Using of special exercises to mtaulp speed to pass the test (150×20) for women football referees - Kassim, Sabah; Sabieh, Nahla (Journal of Physical Education, 2015)
Played football a major role in the development of social and moral point of people, including the poor people, the language of understanding between communities and contributed to the referees played a major role in this aspect, including rulers women must rule women pass the physical tests for the leadership of the match to safety and on this, the researcher studied using exercises to develop mutual speed it and bodily ability to judge in terms of speed and endurance are linked to pass the test 20×150 and was based on sample of the rulers of women in Baghdad ,10 governors dependent second degree chose researcher tests to develop mutual speed are (20×150) (25×8) then used statistical method that fit this researcher and then present and discuss the results through contagious curriculum for 10 weeks containing exercises evolution mtaulp speed women s ability to govern and there for then gave the researcher the most important conclusions and recommendation that fit the study